Yellow fever reemergence in Venezuela – Implications for international travelers and Latin American countries during the COVID-19 pandemic (2021)
In the last few years, Venezuela has been the epicentre for multiple concurrent epidemics (syndemics) of emerging and reemerging infectious and tropical diseases. These events have severe implications for public health control efforts in Latin American and other regions due to the latent threat of case importation. At the top of the list, the resurgence of vector-borne diseases (VBD), such as malaria and dengue pose substantial challenges for the region [5]. On the other hand, the reemergence of vaccine-preventable diseases (VPD) due to low immunization coverage has led to new and multiple outbreaks of measles, diphtheria and other vaccine-preventable infections that are once again affecting many populations.